The link between Human Resource Management Practices and Organisational Performance - Gowda, Sumanth Nagaraja (2017)
This dissertation pursues to present the link between Human resource management practices and Organisational performance. This study is focused on the Information technology industry of UK. It tries to examine and link the HRM practices followed by the UK organisations and their organisational performance through a mediating model. This research study found that none of the human resource management practices have a significant direct link with financial performance, however, it showed that HRM practices are influencing the financial outcomes indirectly through intervening variables and operational performance parameters. This paper begins with the Introduction of HRM practices and its relevance in the modern business environment; then it outlines the problem statement, research questions, objectives and significance of this study. It reviews the literature related to the different conceptual frameworks and some of the previous studies which related HRM practices with Organisational performance, and it also covers the In-depth review of some of the literature on HRM practices and organisational performance parameters. Further, it explains the methodology of the research study which includes the type of research method, data collection and sampling techniques used for the analysis and interpretation of the data. Finally, it reports the statistical analysis of data, results and findings and discuss the implications of the study and then ends it with the conclusion and limitations along with the scope for the future research on this topic.